PENGARUH KOMPOSISI BRIKET BIOMASSA KULIT KACANG TANAH DAN ARANG TONGKOL JAGUNG TERHADAP KARAKTERISTIK BRIKET - Purnawarman, Purnawarman; Nurchayati, Nurchayati; Padang, Yesung Allo (Universitas Mataram, 2015)
Energy crisis in the world especially from fossil fuels which caused by the depletion of non-renewable petroleum reserves. It is therefore necessary to find sources of alternative fuels that are renewable. Biomass is a solid waste that can be used as a fuels source. Peanuts shell and cobs are biomass from agricultural waste which is quite abundant so it is potential to be used as a source of alternative fuels.In this study, peanuts shell biomass combined with charcoal cobs to be made into briquettes by varying the percentage composition of peanuts shell biomass and charcoal cobs as follows 75 : 25, 50 : 50, and 25 : 75. Briquettes that have been printed and then tested its characteristic include heating value, moisture content and ash content.The results show that as the increasing percentage of the charcoal cobs have a significant influence on the characteristic of the briquettes. Briquettes with mix KKT 25 : ATJ 75 has an higher heating value (HHV) and lower heating value (LHV) the highest is equal to 28.718 kJ/kg and 28.279 kJ/kg, and the lowest percentage of moisture content is equal to 5.854%, but the highest result percentage of ash content is equal to 9.326%. Based on the test of these characteristic, biomass briquettes peanuts shell - charcoal cobs meet quality standards that have been established and eligible to became a source of alternative fuels.